Liquid-repellent and thermal insulation HGB/PDMS-CsPbBr3 composite film towards highly great optical property and stability - Yin, Tianyu; Guo, Chiyu; Tao, Liang; Ren, Ke; Yin, Xiaoli; Bi, Chenghao (Journal of alloys and compounds, 2025)
All-inorganic perovskite quantum dots (QDs) have attracted considerable attention in optoelectronic devices due to their impressive advantages, including high quantum efficiency, tunable bandgap, and narrow full width at half maximum. However, the inherent lattice instability distinctly hinders their applications in various extreme environments. Herein, we designed a novel liquid-repellent and thermal insulation composite film by the combination of polydimethylsiloxane (PDMS) and hollow glass bubbles (HGB) with CsPbBr3 QDs. Due to HGB effectively suppressing the thermal stress-induced lattice distortion, the HGB/PDMS-CsPbBr3 composite film performed highly great optical property in a high-temperature environment. The water contact angle (WCA) measured on the prepared HGB/PDMS-CsPbBr3 composite film increased from 62.4 ± 6.5° to 149.5 ± 3.1°. Upon being subjected to sodium hydroxide solution (NaOHaq), the HGB/PDMS-CsPbBr3 composite film could retain its luminescent property for an impressive duration of 30-day immersion. In addition, the HGB/PDMS-CsPbBr3 composite film exhibited a higher photoluminescence quantum yield (PLQY) of 84.9 % and the lower lasing threshold of 0.03 mJ/cm2, indicating a potential of optical gain medium for this composite film. This work is expected to provide an effective strategy to achieve highly stable CsPbBr3 QDs, holding great promise in the future applications of optoelectronic devices. [Display omitted] •HGB/PDMS film effectively passivates internal CsPbBr3 QDs and improves optical properties of CsPbBr3 QDs.•Hydrophobic HGB/PDMS-CsPbBr3 film exhibits stable luminescence in moist environment.•Insulation HGB facilitates CsPbBr3 QDs showing greater stability under heated conditions.